Comparison of optimum finite element method vs. differential quadrature method in two-dimensional heat transfer problem - Fakir, Md. Moslemuddin; Basri, Shahnor; Varatharajoo, Renuganth; Jaafar, Abdul Aziz; Mohd Rafie, Azmin Shakrine; Abang Abdul Majid, Dayang Laila (Praise Worthy Prize, 2008)
Among various numerical solution techniques, finite element method (FEM) and differential quadrature method (DQM) are two important of those. Usually elements are sub-divided uniformly in FEM (conventional FEM, CFEM) to obtain temperature distribution behavior in a fin or plate. Hence, extra computational complexity is needed to obtain a fair solution with required accuracy. In this paper, non-uniform sub-elements are considered for FEM (optimum FEM, OFEM) solution to reduce the computational complexity. Then this OFEM is applied for the solution of two-dimensional heat transfer problem in a rectangular thin fin. The obtained results are compared with CFEM and optimum DQM (ODQM, with non-uniform mesh generation). It is found that the OFEM exhibit more accurate results than CFEM and ODQM showing its potentiality.